PENELITIAN CAMPURAN ASPAL BETON MENGGUNAKAN PASIR VULKANIK GUNUNG KELUD DENGAN LIMBAH BOTOL PLASTIK - Cici Sri Isma Evrilyana; Ahmad Ridwan; Yosef Cahyo Setianto (Faculty of Engineering, Kadiri University, 2018)
The use of a plastic bottle waste mixture on asphalt concrete as an additional material for road pavement is one of the alternatives to get a good quality pavement layer. As well as the innovation of using Mount Kelud volcanic sand as a substitute for Brantas sand. This addition also aims to reduce the amount of plastic waste that is difficult to decipher, in order to reduce the presence of waste so that it does not cause bad impacts on society. This study aims to determine the characteristic properties of asphalt with a mixture of plastic bottle waste. The results of the study, the addition of plastic bottle waste by 2%, 3%, and 5% can be concluded that the addition of 2% plastic bottle waste cannot meet the specifications, but with the addition of plastic bottle waste 3% - 5% it can meet the requirements for the laston mixture specification (AC-BC ).Penggunaan campuran limbah botol plastik pada aspal beton sebagai material tambahan perkerasan jalan salah satu alternatif yang digunakan untuk mendapatkan kualitas lapis perkerasan yang baik. Serta inovasi penggunaan pasir vulkanik gunung kelud sebagai pengganti pasir brantas. Penambahan ini juga bertujuan untuk mengurangi banyaknya sampah plastik yang sulit diuraikan, agar dapat mengurangi keberadaan sampah sehingga tidak menyebabkan dampak buruk bagi masyarakat. Penelitian ini bertujuan mengetahui sifat sifat karakteristik aspal dengan campuran limbah botol plastik. Hasil Penelitian penambahan limbah botol plastik sebesar 2%,3%,dan 5% dapat disimpulakn dengan penambahan platik sebesar 2% belum dapat memenuhi spesifikasi, namun dengan penambahan limbah botol plastik 3% - 5% dapat memenuhi syarat spesifikasi campuran laston (AC-BC).